Decreased Function of Delayed Recall in Non-demented Elderly Subjects With Apolipoprotein E ε4 Allele - Wang, Lijun; Pan, Xiaoli; Fei, Guoqiang; Wang, Changpeng; Wan, Wenbin; Sang, Shaoming; Wang, Hui; Wang, Zhiliang; Zhong, Chunjiu (Frontiers in Aging Neuroscience, 2019)
Apolipoprotein E (APOE) is the major genetic risk factor for late-onset Alzheimer’s disease (AD). Inconsistent results about the role of APOE ε4 alleles on cognitive decline of community non-dementia elderly have been reported. This study aimed to examine the relationship between APOE ε4 allele and cognitive abilities in the subjects aged 60 years or above from a community in Shanghai, China. A total of 1445 participants voluntarily accepted the analysis of APOE genotype and global cognitive assay using the Mini Mental Status Evaluation (MMSE). There were no significant differences in total MMSE scores between APOE ε4 carriers and non-carriers. In addition, the performances of orientation, registration, attention, calculation, and language had no significant differences between subjects with and without APOE ε4 allele. However, stratified analysis showed that the performance of delayed recall in subjects with APOE ε4 allele was inferior to that in non-ε4 carriers (P = 0.041). Further, the multiple linear regression analysis showed the significant correlations between the presence of APOE ε4 allele and the scores of the delayed memory subdomain if age, gender, and education were adjusted but no significant correlations if the related factors were not adjusted. The results indicate that significant impact of APOE ε4 allele only on the delay memory but not on global or other sub-domains of cognitive abilities.